(untitled) (Orfeu, 2018)
This work proposes a discussion of the studies on the musical mind, and reflects on their implications in the academic context of training musicians and teachers in Higher Education. It discusses some problematizations about the gap in knowledge in basic academic formation, and the challenges this presents. The paper also articulates a set of strategies which have been adopted to spread neuroscientific knowledge in the academic context of undergraduate music courses. Finally, this article seeks to deconstruct commonly held myths about the brain and musicality, defending scientific theoretical arguments to support the debate.